Experimental Investigation Into Home Based Biodegradable Material As A Fertilizer Source - Parnon, Mohamad Afiq Amiruddin; Salman, Nur Rabiatul Adawiyah; Hussin, Mohamed Saiful Firdaus (Taylor’s University, 2020)
This project aims to investigate the functional group of hand-made Blackstrap Molasses Fertilizer using Blackstrap Molasses, Epsom Salt, and food wastes. The product was modified to enhance existing fertilizers in terms of environment, time, and cost. Several procedures were carried out started with a collection of food wastes, boiling food wastes with water until the food wastes were fully composted, cooling the food wastes and mixing with additives ingredients (Blackstrap Molasses and Epsom Salt). One type of test was used to test the fertilizer, which was the Fourier Transform Infrared Spectroscopy. The Fourier Transform Infrared Spectroscopy produced graph data that should be interpreted by referring to the spectroscopy chart. The results demonstrated that the wavenumber at peak 1, 2 and 3, which were 3238.9 cm-1, 2363 cm-1 and 1645 cm-1, in Blackstrap Molasses Fertilizer Infrared Spectrum Chart contained amines, phosphorus, and urea in the fertilizer. Amines, phosphorus, and urea are components that are important for plant growth development as these components are based on nitrogen and carbon elements. This study helps to reduce environmental pollution caused by food wastes and provide a more costeffective way of producing fertilizer using food wastes.